Antithesis techniques in the poem "I See You, Tearful and Defiant" by Abu Firas al-Hamdani (Al-Farooq Journal of Sciences, 2026)
This study seeks to explore the "techniques of antithesis" in Abu Firas al-Hamdani's poem Arak 'Asiyya al-Dam (I See You Resisting Tears), employing a structural stylistic approach. It proceeds from the premise that antithesis transcends its mere rhetorical function to become an existential strategy, reflecting the fragmentation of the self between the fragility of the lover and the stoicism of the knight. The study is organized into two main sections: the first addresses the "formative techniques" that establish the focal point of the conflict, while the second examines the "organizational techniques" that regulate emotional chaos. Ultimately, the study concludes that antithesis served as the defensive mechanism that enabled the poet to overcome the tragedy of captivity, transforming his physical defeat into symbolic immortality and a narcissistic triumph that transcends mortality.
Keywords: Stylistics/ Psychological Conflict/ Captivity Literature/ Poetic Mask/ Chivalry/ Duality.